Aplikasi Laporan Tagihan Internet Pada CV. Megadata Berbasis Bot WhatsApp - Maulidiansyah; Ahmad Firman Syahruddin; Ahmad Maula Syahdifa; Andhika Arya Bagaskara; Asrofil Hidayatur Rahman (CV. Shofanah Media Berkah, 2023)
The development of an Internet Bill Report Application at CV. Megadata Based on WhatsApp Bot aims to expedite and minimize errors in delivering customer billing reports. CV. Megadata currently faces challenges in managing their increasingly numerous and diverse customer bills. Many customers make late payments for their monthly bills. This is often due to various reasons, such as customers forgetting about the bills or not having enough funds when the bills are due. To remind customers, CV. Megadata usually sends short messages using the WhatsApp application to prompt customers to make prompt payments. However, this method is considered less effective due to the large number of CV. Megadata customers, resulting in a lengthy process to send all billing messages. Additionally, this method requires precision because administrators often make mistakes in sending billing reports to customers. The data collection methods used in this research are observation and interviews with staff or employees at CV. Megadata. The ultimate output or result of this research is the Internet Bill Report Application at CV. Megadata based on WhatsApp Bot.